The Effect Of Free Sex Education On The Knowledge Of Free Sex In Adolescents In MTs. Maraqitta'limat Medas - rosidi, ahyar; Farlina, Bq. Fina; Suhaemi, Suhaemi; Aini, Nikmatul (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Sexual violence against children is a global issue that is still rampant in many countries around the world and affects children of various vulnerable ages. Sex education does not mean limiting their association with fellow friends, but aims to make them more careful in socializing. The purpose of this study is to determine the influence of sex education on knowledge about free sex in adolescents at MTs. Maraqitta'limat Medas in 2024. Method: Types of pre-experimental research with One Grub pretest-posttest design. A sample of 33 adolescents with a total sampling method. Respondents were given an intervention by providing health education, previously respondents were given a pretest before the intervention and a posttest after the intervention, The measuring tool used was a questionnaire about free sex. Result: The results of the statistical test using the Wilcoxson test with a value of α=0.05 with an average value before the intervention was 8.00 and an average value after the intervention was 16.04. This shows that there is an influence of sex education on the knowledge of free sex in adolescents in MTs. Maraqitta'limat Medas. Conclusion: Based on the results of this study, it is hoped that health workers will be more active in providing education related to promiscuity in adolescents, as an effort to overcome promiscuity that is rampant in the community.